2016
DOI: 10.5194/se-2016-78
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D GPS velocity field and its implications on the present-day postorogenic deformation of the Western Alps and Pyrenees

Abstract: Abstract. We present a new 3D GPS velocity solution for 182 sites for the region encompassing the Western Alps, Pyrenees, and southern France. The velocity field is based on a Precise Point Positioning (PPP) solution, to which we apply a common-mode filter, defined by the 26 longest time series, in order to correct for network-wide biases (reference frame, environmental noise, ...). We show that processing options, such as troposphere delay, can lead to systematic velocity variations of 0.1–0.5 mm yr−1 affecti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
5
7
0
Order By: Relevance
“…In order to calculate formal uncertainties on GPS velocities, we use the formulation of Williams (2003) for continuous stations, which provides velocity standard errors on the basis of the noise characteristics (amplitude and spectral index) of the position time series. We find average spectral indices of À0.8, À0.7, and À0.6 for the north, east, and vertical components, respectively, similar to recent studies (either PPP or double-difference processing; e.g., Hackl et al, 2011;Nguyen et al, 2016;Njoroge et al, 2015;Santamaría-Gómez et al, 2011). These indices are symptomatic of flicker noise (spectral index of À1) with a small component of white noise (index of 0), suggesting a relatively fast convergence of the velocities for long time series (ca.…”
Section: Gps Velocity Uncertaintiessupporting
confidence: 90%
See 1 more Smart Citation
“…In order to calculate formal uncertainties on GPS velocities, we use the formulation of Williams (2003) for continuous stations, which provides velocity standard errors on the basis of the noise characteristics (amplitude and spectral index) of the position time series. We find average spectral indices of À0.8, À0.7, and À0.6 for the north, east, and vertical components, respectively, similar to recent studies (either PPP or double-difference processing; e.g., Hackl et al, 2011;Nguyen et al, 2016;Njoroge et al, 2015;Santamaría-Gómez et al, 2011). These indices are symptomatic of flicker noise (spectral index of À1) with a small component of white noise (index of 0), suggesting a relatively fast convergence of the velocities for long time series (ca.…”
Section: Gps Velocity Uncertaintiessupporting
confidence: 90%
“…Velocities are expressed relative to the stable North American plate, defined in the ITRF2008 reference frame (Altamimi et al, 2012). Nguyen et al (2016) tested several options of the PPP processing in order to estimate the quality of daily positions and deduced velocities. They found that impact of the parameterization choices is mainly dependent to the duration of the time series and could impact velocities up to 0.5 mm/year (mean difference of GPS velocities between several processing options).…”
Section: Gps Data Processingmentioning
confidence: 99%
“…The extension and compression rates for the southern profiles are 3 nanostrain/year and 1 nanostrain/year, respectively. This difference between the northern and southern part of the Western Alps has been pointed out previously by Nguyen et al () on the basis of a correlation between the uplift rates and the mean elevation for the northern region that is absent for the southern part. This is also correlated with the lower topography along the southern profile (Figure ).…”
Section: Using Redundancy Of the Velocity Fields To Decipher The Defosupporting
confidence: 69%
“…This suggested that gravity collapse could play a role in the present‐day deformation of the Western Alps, besides the abovementioned plate tectonic mechanisms. However, Nocquet (), Serpelloni et al (), Nocquet et al (), and Nguyen et al () showed that present‐day uplift of 2+ mm/year is occurring in the northern part of the Western Alps. This prohibits deformation mechanisms such as tectonic extension or gravitational collapse as a unique driving force, as they are both related to regional subsidence.…”
Section: Previous Workmentioning
confidence: 99%
“…-the Western Alps in south-eastern France, the boundary region France-Italy and south-western Switzerland; e.g., Tesauro et al (2006), Delacou et al (2008), Larroque et al (2009), Nguyen et al (2016), Nocquet et al (2016); -the Central/Eastern Alps in Austria and the adjacent regions of Switzerland, Liechtenstein, Germany, Italy and Slovenia; e.g., , , Gosar et al (2007), Sue et al (2007), 30 Brückl et al (2010), Brockmann et al (2012);…”
mentioning
confidence: 99%